Inclusion of Renewable Energy Sources in Municipal Environmental Policy—The Case Study of Kraków, Poland - Tomasz Jeleński; Marta Dendys; Elżbieta Radziszewska-Zielina; Małgorzata Fedorczak-Cisak (Energies, 2021)
This article reviews the evolution of local environmental policy in the context of energy transition and particularly the implementation of RES. The study concerns Kraków, whose policy has been compared with other cities and metropolises and was analysed in a timespan of about 30 years. It was hypothesised that, until recently, RES were treated in the city with reserve concerning their feasibility in local environmental and economic conditions, but since RES have been appreciated as a viable means to effectively combat low-stack emissions, the local air quality targets have been integrated with global decarbonisation goals. This launched a dedicated subsidy stream for RES installations and contributed to the sharp increase in the number of installations. Trend analysis techniques have been used to study environmental indicators in relation to the evolution of municipal policies, the expenditures, and their effects. The review confirms that the implementation of RES had not been a priority for Kraków but a complementary measure to those aimed at improving air quality. The recent integration of the environmental and RES policies has been the next step that is now helping to pursue both the city’s strategic goals: further air quality improvement and climate neutrality by 2050. Kraków may serve as an example of a city that has treated RES in a manner adequate to local conditions and capabilities, thus achieving the intended goals.